Mechatronics Real Time Linux A RTOS Live CD Based on Linux - Aroca, Rafael; Tavares, Dalton; Caurin, Glauco (Anais do Workshop de Sistemas Operacionais (WSO), 2007)
Real Time Operating Systems (RTOS) play a big role when computers are used to control mechanical and electrical devices that need reliable and deterministic control. Although several commercial RTOSes with easy to use interfaces and integrated development environments are available in the market, Linux is being gradually more used because of its low cost and free software philosophy. Potential users, which are not familiarized with Linux, may have trouble setting up a Real Time Linux based system. In this paper we describe the results obtained by tailoring an easy to use Real Time Linux Live CD and the feedback obtained by the realization of mechatronics experiments on undergraduate courses.